(untitled) (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
Madhya Pradesh state is forced to optimize the utilization of its water resources due to continuous depletion of the fossil fuels and its present power generation scenario. The state has two cascade schemes of hydro-electric plants one at Chambal river and the other at Narmada river. Narmada river at present has four main hydro plants in cascading mode starting from Bargi, Indira Sagar and Omkareshwar in Madhya Pradesh to Sardar Sarovar in the neighboring state of Gujrat. The installed capacities of 2810 MW of these hydro plants feed to the major portion of state’s electricity demand. The proper scheduling of the hydroelectric plants mean, water resources must be used in such a way that, water discharge at an upstream plant is converted into electric energy at downstream plants without spillage. Hydroelectric scheduling of the plants requires a judicious modeling of each of the hydro electric plant for an improved efficiency and arrest possible losses. The paper presents the mathematical model of the Omkareshwar hydroelectric plant as part of cascade scheme at Narmada River in Madhya Pradesh. Key words: Hydro-electric system, hydro turbine model, reservoir model, tailrace model, water flow equation. Hydro Nepal: Journal of Water, Energy and Environment Issue No. 3, January, 2008 Page 48-52